2019
DOI: 10.21608/ejabf.2019.25929
|View full text |Cite
|
Sign up to set email alerts
|

Basic Parameters for Assessment and Management of the Short-Finned Squid Illex coindetii (Verany, 1839) (Cephalopoda, Ommastrephidae) from the deep water off the Egyptian Mediterranean Sea.

Abstract: Short-Finned Squid Growth parameters Mortality Spawning periodThis research is the first study of Illex coindetii from the deep sea fishing ground adopted in the Egyptian Mediterranean Sea. That assist to prevent stock reduction by estimation of growth parameters, mortality, and size at maturity which taken as a reference point of minimum legal size to prevent stock depletion. Specimens of Illex coindetii were collected from bottom trawl vessels at 250:850 m depths from the Egyptian Mediterranean Sea. A total … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…In deep waters of the Egyptian Mediterranean Sea, growth parameters, mortality, and size at maturity were estimated for the first time. Estimated exploitation rates suggested that the stock was overexploited, and that overexploitation was higher in females than males (Amin and Sabrah, 2019).…”
Section: Fishery Management and Conservationmentioning
confidence: 99%
“…In deep waters of the Egyptian Mediterranean Sea, growth parameters, mortality, and size at maturity were estimated for the first time. Estimated exploitation rates suggested that the stock was overexploited, and that overexploitation was higher in females than males (Amin and Sabrah, 2019).…”
Section: Fishery Management and Conservationmentioning
confidence: 99%
“…The pattern of growth and conditions factor of fish can be identified by measuring the length and weight of fish [Shalloof and El-Far, 2017;Lanzoni et al, 2018;Karna et al, 2018;Philips, 2019;Amin and Sabrah, 2019]. Several studies were conducted to examine the relationship between the length and weight of Mudskipper fish.…”
Section: Introductionmentioning
confidence: 99%